The Obstacles and Challenges of Women Workers in the Construction Industry - Salamah, Ummu; Widaningsih, Lilis (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
Construction is an industry that contains activities to create or build facilities and infrastructure in a tangible form in order to achieve certain goals. It is known as a male-dominated industry with heavy work, which creates gaps and problems for the women who work there. The purpose of this study is to provide an overview of the obstacles and challenges of women when working in the construction industry. This study uses a qualitative approach with a literature review method. Article searches are performed through the Publish or Perish application on the Scholar platform. After screening through inclusion and exclusion criteria, there were 25 scientific articles from 9 international journals that met the criteria. The result is that the obstacles and challenges faced by women in the construction industry are classified into internal and external. Internal obstacles in the form of: mental readiness, lack of competence, not having a certificate of expertise in a particular field; while the external obstacles are: discrimination based on gender, sexual harassment, lack of organizational support, and disparity in workers' wages. Internal challenges in the form of: self-efficacy, openness, fatigue and work stress; while the external challenges are: high work pressure, long working hours, heavy workload, and masculine culture. To overcome these problems, it requires not only the efforts of each individual, but also the cooperation of all parties involved, especially policy makers in companies and government.